Feasibility of Early Active Rehabilitation for Concussion Recovery in Youth: A Randomized Trial. Issue 6 (November 2020) - Dobney, Danielle M.; Grilli, Lisa; Beaulieu, Christine; Straub, Meghan; Galli, Carlo; Saklas, Mitchell; Friedman, Debbie; Dubrovsky, Alexander Sasha; Gagnon, Isabelle J.
Abstract : Objective: The primary objective is to evaluate the feasibility (safety and acceptability) of implementing early active rehabilitation (AR) for concussion management in youth with symptoms persisting 2 weeks after injury. A secondary and exploratory objective was to estimate the potential efficacy of early AR compared with standard AR. We hypothesize that AR at 2-weeks postconcussion will be safe and acceptable to patients. Design: Randomized clinical trial. Setting: The Montreal Children's Hospital of the McGill University Health Center (MCH-MUHC), a tertiary care pediatric teaching hospital affiliated with McGill University in Montreal, Canada. Participants: Twenty youth aged 9 to 17 years old with postconcussion symptoms for at least 2 weeks. Intervention: Active rehabilitation (aerobic exercise, coordination drills, visualization, and education/reassurance) was administered by physiotherapists in-person, and then continued as a home program. Methods: Twenty participants were randomized to either early AR (initiated 2 weeks after injury) or standard AR (initiated 4 weeks after injury). Results: Two adverse events (one in each group) were identified through an online survey more than one-month postconcussion. Postconcussion symptoms decreased over time for both groups. Conclusions: The results from this pilot study indicate that a full clinical trial estimating the efficacy of early AR (starting 2 weeks after injury) is feasible. Further study is needed to determine the superiority of this strategy over current treatment approaches. Abstract : Supplemental Digital Content is Available in the Text.